Medical and Mental Health During Childhood Psychosocial Perspectives and Positive Outcomes - Nabors, Laura (Springer Series on Child and Family Studies, 2016)
This textbook provides a comprehensive overview of medical and mental illness in children, detailing how psychological, academic, and social functioning can be enhanced - and inherent challenges overcome - in young patients. The volume describes best-practices in depth, including how to ensure accurate diagnosis, developmentally appropriate treatment, and effective coordination between medical and school personnel. It discusses common medical conditions (e.g., asthma, cancer, diabetes) and mental health conditions (e.g., autism, ADHD, depression), emphasizing the critical role of health education in promoting optimal outcomes. Topics featured in this text include:  Screening and diagnosis practices for children with medical and mental illness.  Chronic and condition-related pain in children. Medical fears that may interfere with treatment and positive health behaviors Health education and coping strategies for children. Recommendations for family-directed interventions. Illustrative case studies and review questions. Medical and Mental Health During Childhood is an essential text for graduate students as well as a valuable reference for researchers, professors, and clinicians in clinical child and school psychology, social work, public health, family studies, educational psychology and counseling, health education, and allied disciplines.